2002
DOI: 10.1080/713604351
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic microsurgical tubal reanastomosis: a preliminary study

Abstract: In our preliminary study, the pregnancy rate was 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…In the study [21] by Yoon et al, it was reported that there was a statistically significant difference in the pregnancy rate between patients who underwent bilateral anastomosis and those who underwent unilateral anastomosis; however, Isaacs et al and Çetin et al reported that the pregnancy rates in unilateral or bilateral anastomosis were not different [16,22]. In addition to that, the patient receives less anesthesia and the surgical team's performance is better during a unilateral anastomosis because of the shortened operation time (success is higher with shorter operation times).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the study [21] by Yoon et al, it was reported that there was a statistically significant difference in the pregnancy rate between patients who underwent bilateral anastomosis and those who underwent unilateral anastomosis; however, Isaacs et al and Çetin et al reported that the pregnancy rates in unilateral or bilateral anastomosis were not different [16,22]. In addition to that, the patient receives less anesthesia and the surgical team's performance is better during a unilateral anastomosis because of the shortened operation time (success is higher with shorter operation times).…”
Section: Discussionmentioning
confidence: 91%
“…This could be particularly beneficial for a patient who has had a previous laparotomy or Cesarean section, because this approach allows her to avoid a second laparotomy. Laparoscopic tubal re-anastomosis is a good alternative to classical microsurgery in patients who desire the reversal of tubal sterilization, and it may be considered to be the procedure of choice for surgeons who have extensive experience with tubal anastomosis by laparotomy and advanced laparoscopic techniques [16]. Surgery and ART are complementary approaches that can be used singly or in combination to improve the outcome for couples with tubal infertility [30].…”
Section: Discussionmentioning
confidence: 99%
“…38 En su contra pesan la necesidad de laparoscopios con magnificación, la dificultad técnica, mayor tiempo quirúrgico (201 minutos para laparoscopia vs. 148 minutos para microcirugía) 39 y costos superiores a la microcirugía. 40 En nuestro hospital hacemos cirugía laparoscópica para otras indicaciones; no hemos intentado la recanalización post-ligadura de trompas, debido a que la microcirugía es un procedimiento muy sencillo con 2 a 3 horas de duración, y con 1 a 2 días de hospitalización.…”
Section: Discussionunclassified